First record of Stiphodon annieae Keith & Hadiaty, 2014 (Teleostei, Oxudercidae) from Sulawesi Island, Indonesia - Gani, Abdul; Nurjirana, Nurjirana; Bakri, Achmad; Adriany, Devita; Wuniarto, Erwin; Khartiono, Lady; Satria, Dawam Heksa; Hasan, Veryl; Herjayanto, Muh; Burhanuddin, Andi Iqbal; Moore, Abigail Mary; Kobayashi, Hirozumi (Check list (Luís Felipe Toledo), 2021)
The recently described Stiphodon annieae (Keith & Hadiaty, 2014) was thought to be endemic to Halmahera Island, Indonesia. However, from August 2019 to January 2020, we collected several specimens during field trips to the Soho, Simpong, and Uso rivers in Luwuk Banggai, Central Sulawesi, Indonesia. We describe specimens collected in the Soho River and discuss the ichthyofauna of Luwuk Banggai. This is the first report of S. annieae from Sulawesi. Our records represent a range extension of approximately 500-600 km west of this species' type locality on the island of Halmahera.